Building futures oriented universities. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
In 1962 the company Humble Oil ran an advertising campaign that claimed “Each day Humble supplies enough energy to melt 7 million tons of Glacier”. Today this advertisement seems bizarre! It is likely that to a future generation the Lisbon Declaration, issued by the European University Association in 2000, which set a 2010 European target of becoming: “the most competitive and dynamic knowledge-based economy in the world, capable of sustainable economic growth, with more and better jobs, and greater social cohesion”1 will seem equally hapless. After all, there is no mention of the environment, of a relevant ethically oriented values base, of a wider human context, nor of a vision reaching beyond the narrow economy and social maintenance of the status quo.